2018
DOI: 10.1159/000496700
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Improves Short-Term Growth in Patients with Temple Syndrome

Abstract: Background/Aims: Temple syndrome is an imprinting disorder caused by maternal uniparental disomy of chromosome 14 (mat UPD14), paternal deletion of 14q32 or paternal hypomethylation of the intergenic differentially methylated region (MEG3/DLK1 IG-DMR). Patients with Temple syndrome have pre- and postnatal growth restriction, short stature, hypotonia, small hands and feet and precocious puberty. We sought to determine whether treatment with growth hormone improves growth outcomes in patients with Temple syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Also, in our prepubertal group, height SDS increased significantly over the course of 1 year of GH treatment. A previous study in seven GH-treated patients with TS14 showed a similar improvement of height SDS [13]. However, that group had a lower starting median height SDS and a lower median age at initiation of GH treatment, compared to our group.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Also, in our prepubertal group, height SDS increased significantly over the course of 1 year of GH treatment. A previous study in seven GH-treated patients with TS14 showed a similar improvement of height SDS [13]. However, that group had a lower starting median height SDS and a lower median age at initiation of GH treatment, compared to our group.…”
Section: Discussionsupporting
confidence: 65%
“…Not only an early pubertal growth spurt but also treatment with GnRHa can influence height, weight, and body composition. One retrospective study in 7 GH-treated patients with TS14 showed an increased growth after 1 year of GH treatment [13]. Another paper described the effects of GH treatment in 2 patients (aged 6.9 and 9.3 years) with TS14 and found that both height SDS and body composition improved during 2 years of treatment [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, four patients were receiving GH treatment at the time of the study, and two had received GH until reaching adult height. As GH treatment has been proven to improve growth [ 35 ], this could possibly explain that an average height SDS was found at the time of examination. Several patients in our study had precocious puberty and had gone through their pubertal growth spurt at a young age and most had been treated with puberty-inhibiting GnRH (Gonadotropin Releasing Hormone) analogues.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a lot of literature supporting GH treatment in PWS, there is very little research done in children with PWL. In a small group of patients with Temple syndrome, GH treatment was shown to improve growth (94). In a retrospective study in 26 patients with SYS, of which 14 had been treated with GH, it was shown that GH increased body height and decreased body mass index in the first months of treatment (95).…”
Section: Potential Treatment Optionsmentioning
confidence: 99%